Oral Dimensions Related to Bit Size in Adult Horses and Ponies - Anttila, Mirjami; Raekallio, Marja; Valros, Anna (Frontiers in Veterinary Science, 2022)
A bit that fits is essential for horse welfare and good communication with the ridden, driven or led horses. The bit causes pressure on the sensitive structures of the horse mouth. The aim of this study was to investigate variation in oral dimensions related to bit fit in adult horses and ponies and to evaluate bit fit by comparing oral dimensions with the currently used bit size selected by the horse owner. The study population consisted of 554 horses and ponies, 308 geldings and 246 mares, age 5 to 29 years, presented for routine dental care. Oral dimensions: mouth width, distance between upper and lower jaw, tongue thickness and lower jaw width, were measured under sedation. Oral dimensions were compared with the most used bit mouthpiece size presented to the researcher by the owner. Bit type and material were recorded. All oral dimensions in adult horses and ponies varied by breed and sex. Mouth width and distance between upper and lower jaw correlated positively with age. Oral dimensions were significantly smaller in mares than in geldings. In coldblood Finnhorses, oral dimensions were greater than in other breeds; in ponies they were smaller. The majority of the oral dimensions correlated positively with each other. Lower jaw width did not correlate with tongue thickness. It was common to use a bit that did not fit¬ the horse: the bit was either too short or too long (over 10 mm longer) compared to mouth width, compressed the tongue in between the upper and lower jaw, or the center link was of similar length compared to lower jaw width, thus possibly causing pressure points or a nutcracker effect on the bars of the lower jaw. Horses had, on average, space for a 14 mm thick bit without compressing the tongue. The results of this study can aid in choosing a horse bit size that fits correctly and does not cause discomfort. It is recommended that the fit of the bit is evaluated regularly as the horse ages.